Spontaneous regression of fetal pleural effusion in pregnancy complicated with Herpes simplex infection: Clinical presentation and literature review - Szewczuk, Oksana; Szewczuk, Wiktor; Walędziak, Maciej; Różańska-Walędziak, Anna (European journal of obstetrics & gynecology and reproductive biology, 2024)
•Management of fetal pleural effusion depend on the dynamics and volume of the fluid compartment.•Connection between Herpes virus infection and fetal pleural effusion are no determined yet.•The incidence of fetal pleural effusion is low and the neonatal outcomes difficult to be predicted.•The management of fetal pleural effusion should be subject to further studies to determine the best clinical practice. Fetal primary hydrothorax is a rare congenital anomaly with an estimated incidence of 1:10,000–15,000 pregnancies, with an unpredictable clinical course, ranging from spontaneous resolution to fetal death. A case of unilateral fetal pleural effusion was diagnosed at 35th week of gestation during a routine ultrasonographic fetal assessment in an uncomplicated pregnancy. A large echogenic collection of fluid was revealed in the right pleural cavity, together with atelectasis of the right lung, as well as displacement of heart and mediastinal structures to the left side of thorax. The patient was also diagnosed with polyhydramnios and there was a disproportion of heart ventricles volume. No other fetal structural abnormalities were detected and there were no symptoms of edema. Fetal biometrics was consistent with the gestational age. In echocardiography, fetal heart was structurally and functionally normal. Screening tests for congenital infections of the fetus were negative. Autoimmune fetal hydrops was excluded after laboratory tests. There was no parents’ consent for the analysis of the karyotype. The patient presented clinical symptoms and was diagnosed with Herpes simplex virus infection and was treated with oral acyclovir. Serial fetal ultrasound exams showed gradual decrease in pleural fluid volume up to complete resolution in 38th week of pregnancy. Pregnancy was ended in the 38th week of gestation with a cesarean delivery of a healthy neonate. It is yet to be determined if there is a direct association between Herpes simplex virus infection in pregnancy and the risk of fetal pleural effusion. The incidence of fetal pleural effusion is low and the neonatal outcome difficult to be predicted. The optimum management of fetal pleural effusion should be subject to further studies to determine the best clinical practice.